Characterization of strict local minimizers of order two for semi -infinite problems in the nonparametric constraint case - A. Taha, Abdul Wahab (Iraqi Journal of Science, 2022)
We extended the characterization of strict local minimizers of order two in ward,stheorem for nonlinear problem to a certain class of nonsmooth semi-infinite problems with inequality constraints in the nonparametric constraint case.